Statistical based algorithm for reducing bit stuffing in the Controller Area Networks. (July 2020) - Alaei, Reza; Moallem, Payman; Bohlooli, Ali
Abstract: One of the problems with the Controller Area Network is jitter of response time because of the bit-stuffing mechanism. In real-time cases where timing accuracy is important, jitter may deteriorate the quality of the control procedure noticeably. A new method based on XOR masking, named Statistical Mask Calculation (SMC), is presented in this study. The method uses the statistical parameters of data to generate a proper mask for each case. The performance of the proposed method on the reduction of the number of stuff bits is evaluated by considering real data set and a comparison with existing original XOR masking is done. The results indicate that applying the proposed method on the case study increases the probability of zero bit stuffing up to 46% compared to the original XOR mask. It should be noted that the proposed technique is more effective for systems that are usually predictable. Therefore, the adaption of this technique depends on the required application.